Evolusi Metode Pembelajaran dengan Teknologi: Kajian Literatur Tentang Efektivitas dan Tantangannya - Lili Liana; A Roen, Yeheskial; Bataragoa, Efrita (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This research examines the evolution of technology-enabled learning methods and their effectiveness and challenges through in-depth literature analysis. The research method in this study uses the literature method. The results show that educational technology has undergone rapid development and proven to enhance interaction, personalisation and accessibility in the teaching and learning process. E-learning platforms, educational apps and other digital tools can enrich students' learning experience and support flexibility in learning. However, the study also identified a number of challenges, such as the digital divide that hinders equitable access to technology, limited digital skills among teachers and students, and privacy and data security concerns. To maximise the benefits of technology in education, collaborative efforts are needed that include infrastructure investment, intensive training for educators and the implementation of policies that ensure safe and inclusive use of technology. The results of this study are expected to provide valuable insights for policy makers, educators and researchers in advancing technology integration in the education system.